Production of greenhouse gas free hydrogen by thermocatalytic decomposition of methane – A review - Ashik, U.P.M.; Daud, Wan Mohd Ashri Wan; Abbas, H.F. (Elsevier, 2015)
Thermocatalytic decomposition of methane (TCD) is a fully green single step technology for producing hydrogen and nano-carbon. This review studying all development in laboratory-scale research on TCD, especially the recent advances like co-feeding effect and catalyst regeneration for augmenting the productivity of the whole process. Although a great success on the laboratory-scale has been fulfilled, TCD for greenhouse gas (GHG) free hydrogen production is still in its infancy. The need for commercialization of TCD is greater than ever in the present situation of huge GHG emission. TCD usually examined over various kind of catalysts, such as monometallic, bimetallic, trimetallic, combination of metal-metal oxide, carbonaceous and/or metal doped carbon catalysts. Deactivation of catalysts is the prime drawback found in TCD process. Catalyst regeneration and co-feeding of methane with other hydrocarbon are the two solutions put forwarded in accordance to overcome deactivation hurdle. Higher amount of co-feed hydrocarbon in situ produce more amount of highly active carbonaceous deposits which assist further methane decomposition to produce additional hydrogen to a great extent. The methane conversion rate increases with increase in the temperature and decreases with the flow rate in the co-feeding process in a similar manner as observed in normal TCD. The presence of co-components in the post-reaction stream is a key challenge tackled in the co-feeding and regeneration. Hence, this review hypothesizing the integration of hydrogen separation membrane in to methane decomposition reactor for online hydrogen separation. (C) 2014 Elsevier Ltd. All rights reserved.